Función cuadrática y ecuación de segundo grado desde la ingeniería didáctica - LAZARTE, Graciela; REY GENECIO, María; FORCINITO, Silvia; HERNANDEZ, Clarisa (UNION MATEMATICA ARGENTINA, 2003)
Docentes de la U.N.Jujuy